Intrauterine retention of fetal bones, a cause for secondary infertility - Humane, Anil; Agrawal, Nikita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Secondary infertility due to retained products of conception in the form of fetal bones is a rare entity. It is usually associated with a history of abortion, either spontaneous or induced. The bony fragments probably act as an intrauterine contraceptive device to stimulate the secretion of endometrial prostaglandins, resulting in secondary infertility. The common symptoms include menstrual disturbances, pelvic pain, dyspareunia, vaginal discharge, spontaneous passage of fetal bones and infertility. Advanced diagnostic technique like hysteroscopy has helped in the diagnosis.